Stem extract from Costus afer (Bush cane) prevents ethanol-induced neuronal degeneration in mice via an antioxidant-inflammatory pathway - Agnes Igimi Odey; Sunday A. Bisong; Iliya Ezekiel; Ejike Daniel Eze; Solomon Emmanuel Nachamada; Ayomide Victor Atoki; Olufunke Onaadepo; Patrick Maduabuchi Aja (Phytomedicine Plus)
Background: Excessive alcohol consumption is associated with memory impairment and can lead to Alzheimer's disease-like dementia, contributing to the rising prevalence of dementia worldwide. Costus afer (Bush cane) is a medicinal plant widely used in traditional African medicine for its anti-inflammatory, antioxidant, and neuroprotective properties. It is commonly employed to treat various ailments, including inflammatory diseases, respiratory conditions, and gastrointestinal disorders. Purpose: Given its traditional use in the treatment of kyphosis (hunchback) which is implicated in cerebral palsy and degenerative disease of the spine, we explored its potential neuroprotective effects against ethanol-induced neuronal degeneration, in this research, we examined the potential protective impacts on memory and neurology afforded by the aqueous stem extract derived from C. afer in mice subjected to ethanol exposure. Methods: Forty-five male Swiss mice weighing 22–35 g were divided into five groups (n = 9): control (treated with distilled water orally), memory-impaired (treated with ethanol at 5 g/kg orally), and three groups treated with ethanol followed by administration of C. afer at doses of 100 mg/kg, 200 mg/kg, and 500 mg/kg respectively. All animals were provided unrestricted access to both food and water throughout the duration of the study. Memory impairment was assessed after 28 days using the T-maze spontaneous alternation test. Subsequently, spectrophotometry, ELISA, and histomorphometry were employed to evaluate indicators of neuronal inflammation, oxidative stress linked to inflammation, and degenerative changes were assessed in the hippocampus, prefrontal cortex, and cerebellum. Results: Ethanol administration led to a notable (p < 0.01) decline in neurobehavioral function, as evidenced by reduced spontaneous alternation behavior, which was mitigated by C. afer treatment, leading to increased percentage alternation. Furthermore, ethanol administration altered endogenous antioxidant levels and pro-inflammatory mediators, resulting in elevated lipid peroxidation, nitrite, tumor necrosis factor-alpha, interleukin-6, and decreased superoxide dismutase activity, promoting neuronal degeneration in the mice brains. However, treatment with C. afer at doses of 100 mg/kg, 200 mg/kg, and 500 mg/kg substantially (p < 0.05) attenuated oxidoinflammatory stress by reducing levels of MDA, NO-2, TNF-α, IL-6, while upregulating SOD activity, thereby preserving neuronal integrity in the hippocampus, prefrontal cortex, and cerebellum. Conclusion: These findings suggest that C. afer mitigates the progression of memory impairment induced by ethanol through mechanisms involving the suppression of oxidoinflammatory stress facilitators and inhibition of cortico-hippocampal and cerebellar neuronal degeneration in murine subjects.